Abortion from an Islamic Perspective: Permission and Prohibition Positions - Mohammed, Alqahtani Jawhrah (International Journal of Innovative Research in Medical Science, 2020)
Abortion is a common controversial ethical issue among humanists, feminists, liberals, and religious groups worldwide. Many countries permit induced abortion, or the deliberate termination of pregnancy, for various reasons e.g., as a means of contraception, as part of a woman’s right to autonomy, or as part of a woman’s right to determine the number of children she will bear. Even in Islamic countries, which hold strong religious laws and beliefs, it has been announced that abortion may be permissible before or after the period of “ensoulment” in certain circumstances and on medical grounds, so as to safeguard women from serious problems that might put their lives at risk. However, some religious groups do not support abortion. Therefore, it is critical to explore Islam’s position on the prohibition or allowance of induced abortion.